The Influence of Work-Life Balance and Transformational Leadership on the Performance of Educational Staff via Organizational Citizenship Behavior in Higher Education - Yenti, Sylvia Rahma; Afriyeni, Afriyeni (International Journal of Multidisciplinary Research of Higher Education, 2025)
This study aims to analyze the influence of work-life balance and transformational leadership on the performance of educational staff in higher education institutions, with Organizational Citizenship Behavior as an intervening variable. The research employs a quantitative approach using path analysis, involving all 34 educational staff members as the sample. Data were collected through questionnaires and analyzed using validity and reliability tests, normality, multicollinearity, and heteroscedasticity tests, followed by hypothesis testing using Sobel tests and path analysis by using SPSS application. The results indicate that Organizational Citizenship Behavior significantly mediates the effect of both work-life balance and transformational leadership on employee performance. Work-life balance contributes to employees’ well-being and encourages voluntary behaviors such as helping colleagues and taking initiative, which in turn enhance overall performance. These findings suggest that organizations, should implement policies that support work-life balance and promote transformational leadership to create a conducive work environment. Encouraging Organizational Citizenship Behavior can further strengthen the positive effects of these factors on performance. Therefore, integrating work-life balance, transformational leadership, and Organizational Citizenship Behavior into human resource management strategies is essential for achieving sustainable and effective organizational outcomes. This study provides empirical evidence and theoretical contributions to the understanding of how Organizational Citizenship Behavior mediates the relationship between work-life balance, transformational leadership, and employee performance in an academic setting.